HOMECARE: STRATEGY OF THE BIOPOLITICS? - Oliveira, Stefanie Griebeler; Kruse, Maria Henriqueta Luce; Echevarría-Guanilo, Maria Elena; Velleda, Kimberly Larroque; Santos-Junior, José Ricardo Guimaraes dos; Sartor, Silvia Francine (Journal of Health Care, 2017)
Objective: To analyze the approaching of homecare as strategy of biopolitics by characterizing the publications that are published worldwide. Methods: It is a bibliographic research, a narrative review, which had its searches found at PubMed, in March 2015, and had as descriptors: home care services; patient care team; homebound persons; caregiver. 2,920 publications were found, from which 142 peer-review articles were selected. The analysis was based on Foucault’s perspective. Results: Most part of the publications has its origin in developed countries, and has caregivers, chronic patients, and patients with advanced cancer as the most present and researched subjects. Experts and institutions produce most part of the publications. Oncology, palliative care, nursing education, social psychology, and others, are the areas of knowledge that are most connected to the home care theme. Conclusion: Home care consists in a strategy of biopolitics, once it emerges according to the necessities of population’s morbidity; it approaches two populations: patients and caregivers; there is a group of experts and institutions that utter and organize the knowledge on the theme.